2000
DOI: 10.1046/j.1460-9568.2000.00162.x
|View full text |Cite
|
Sign up to set email alerts
|

Connexin43 phosphorylation state and intercellular communication in cultured astrocytes following hypoxia and protein phosphatase inhibition

Abstract: The effects of hypoxia and phosphatase inhibitors on connexin43 (Cx43) phosphorylation state, gap junctional intercellular communication (GJIC) and immunolabelling with anti-Cx43 antibodies were investigated in cultured astrocytes. Astrocytes contained predominantly phosphorylated forms of Cx43 and these underwent dephosphorylation 30 min after hypoxia. This was preceded by a 77% reduction in GJIC 15 min after hypoxia, indicating that reduced GJIC occurs prior to Cx43 dephosphorylation. Hypoxia caused a reduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
84
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(92 citation statements)
references
References 39 publications
7
84
1
Order By: Relevance
“…Consistent with previous findings (Giaume et al, 1991;Li and Nagy, 2000), the astrocytes matured in vitro in this study expressed Cx43. Treatment of the astrocytes with CNTF or CNTFR␣ alone caused no detectable alteration in total Cx43 protein levels compared with vehicle ( Figure 2, A and B).…”
Section: Cntf Complex Increases Cx43 Protein Expression and Intercellsupporting
confidence: 93%
“…Consistent with previous findings (Giaume et al, 1991;Li and Nagy, 2000), the astrocytes matured in vitro in this study expressed Cx43. Treatment of the astrocytes with CNTF or CNTFR␣ alone caused no detectable alteration in total Cx43 protein levels compared with vehicle ( Figure 2, A and B).…”
Section: Cntf Complex Increases Cx43 Protein Expression and Intercellsupporting
confidence: 93%
“…This could be due a decreased rate of phosphorylation and/or an increased rate of dephosphorylation of these proteins. It should be noted that hypoxia has been reported to increase activities of the protein phosphatases protein phosphatase 1 (28), calcineurin (34), and tyrosine phosphatase (16) in a number of cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Astrocytic Cx43 was described to contribute to the propagation of stress signals from cell to cell after ischemic brain injury, and Cx30 was found to be highly regulated in the hippocampus after hypoxic conditions in young mice, while Cx43 expression remained unchanged (Frantseva et al, 2002;Zeinieh et al, 2010). Additional studies on regulation of gap junction channels under hypoxic conditions revealed dephosphorylation of Cx43 and loss of intercellular coupling in cultured astrocytes (Li and Nagy, 2000). In Cx30/Cx47-deficient mice, the fine regulation of Cx30 channels after hypoxia is not operative, and a potential closure of Cx43 channels between astrocytes under these conditions might result in increased lesion size in Cx30 Ϫ/Ϫ /Cx47 Ϫ/Ϫ mice.…”
mentioning
confidence: 96%